THE SCHOLARSHIP - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
A scholarship is a form of financial aid awarded to students to further education. Scholarships are awarded based upon various criteria, such as academic merit, diversity and inclusion, athletic skill, and financial need. Scholarship criteria usually reflect the values and goals of the donor or founder of the award